Nano-Bio- Electronic, Photonic and MEMS Packaging - Wong, C.P.; Moon, Kyoung-Sik.; Li, Yi (Grace).; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Nanotechnologies are frequently being applied to the biotechnology area, especially in nano material synthesis. Until recently, there has been little research into how to implement nano/bio materials at the device level. Nano-Bio- Electronic, Photonic and MEMS Packaging discusses how nanofabrication techniques can be used to customize packaging for nano devices with applications to biological and biomedical research and products. Covering such topics as nano bio sensing electronics, bio device packaging, NEMs for bio devices and much more, including: Offering a comprehensive overview of nano and bio packaging Discussing nano materials as power energy sources Analyzing nanotubes, superhydrophobic self-clean Lotus surfaces Covering nano chemistry for bio sensor / bio medical device packaging Nano-Bio- Electronic, Photonic and MEMS Packaging is the perfect book for all biomedical engineers, industrial electronics packaging engineers, and those engaged in bio nanotechnology applications research. .
Nanomaterials for Microelectronic and Bio-packaging -- Nano-conductive Adhesives for Nano-electronics Interconnection -- Biomimetic Lotus Effect Surfaces for Nanopackaging -- Applications of Carbon Nanomaterials as Electrical Interconnects and Thermal Interface Materials -- Nanomaterials via NanoSpray Combustion Chemical Vapor Condensation, and Their Electronic Applications -- 1D Nanowire Electrode Materials for Power Sources of Microelectronics -- Mechanical Energy Harvesting Using Wurtzite Nanowires -- Nanolead-Free Solder Pastes for Low Processing Temperature Interconnect Applications in Microelectronic Packaging -- to Nanoparticle-Based Integrated Passives -- Thermally Conductive Nanocomposites -- Physical Properties and Mechanical Behavior of Carbon Nano-tubes (CNTs) and Carbon Nano-fibers (CNFs) as Thermal Interface Materials (TIMs) for High-Power Integrated Circuit (IC) Packages: Review and Extension -- On-Chip Thermal Management and Hot-Spot Remediation -- Some Aspects of Microchannel Heat Transfer -- Nanoprobes for Live-Cell Gene Detection -- Packaging for Bio-micro-electro-mechanical Systems (BioMEMS) and Microfluidic Chips -- Packaging of Biomolecular and Chemical Microsensors -- Nanobiosensing Electronics and Nanochemistry for Biosensor Packaging -- Molecular Dynamics Applications in Packaging -- Nanoscale Deformation and Strain Analysis by AFM/DIC Technique -- Nano-Scale and Atomistic-Scale Modeling of Advanced Materials.
Keywords: Materials science; Electrochemistry; Biophysics; Biological physics; Electronics; Microelectronics; Biomedical engineering; Nanotechnology; Materials Science; Nanotechnology; Electrochemistry; Electronics and Microelectronics, Instrumentation; Biomedical Engineering; Biophysics and Biological Physics; Electronic books